(untitled) (Bangladesh Journal of Pharmacology, 2017)
Boerhavia procumbens is a medicinal herb used in the treatment of various ailments including asthma, cough and jaundice. The concentration of calcium (280.7 ± 0.0 mg/100 g, 102.3 ± 0.0 mg/100 g), potassium (240.4 ± 0.0 mg/100 g, 92.1 ± 0.0 mg/100 g), aspartic acid (30.9 ± 0.0 g/100 g, 26.1 ± 0.0 g/100 g), glutamicacid (25.2 ± 0.0 g/100 g, 17.7 ± 0.0 g/100 g) and alanine were the abundant in the stem and root than leaf while carbohydrate (79.9 ± 0.0%) was found higher in the leaf of B. procumbens. The leaf and root extracts revealed the presence of alkaloids, flavonoids, tannins and phenol. Leaf extract was found to be more active against S. aureus (11.5 ± 0.3 mm), C. michiganensis (12.1 ± 0.2 mm) and F. oxysporum (23.6 ± 0.2 mm) than the root extract of B. procumbens. It is concluded that stem and root of B. procumbens contain essential nutrients and the antimicrobial study encourages the use of leaf extract for the treatment of most common microbial diseases. Video Clip of Methodology: 4 min 54 sec Click to watch